Notfallmedizin abseits schnell erreichbarer medizinischer Infrastruktur - Leischker, Andreas; Holst, Fritz GE (DMW - Deutsche Medizinische Wochenschrift, 2018)
For many acute diseases and injuries, treatment does not differ between industrialised environment and wilderness setting. However, for some emergencies, treatment needs to be adapted if advanced medical care facilities cannot be reached within 4 hours.In these situations, dislocated joints and fractures should be reduced quickly. Contaminated wounds should be cleaned carefully, with drinking water being sufficient when no sterile solution is available. A patient with a contaminated wound should receive a systemic antibiotic coverage within one hour. Keeping an injured patient warm is crucial to prevent disseminated coagulation.In most cases in the wilderness, cardiopulmonary resuscitation (CPR) should be stopped after 20 minutes; if no return of spontaneous circulation (ROSC) has occurred. However, in case of severe hypothermia, drowning or cardiac arrest due to lightning, prolonged CPR may be feasible.Handwashing with soap and water and use of alcohol gels are effective measures for the prevention of travellers’ diarrhoea during expeditions.
Keywords: Wilderness Medizin; Hypothermie; Reisediarrhö; Kardiopulmonale Reanimation